4-Fluoromethamphetamine (4-FMA) induces in vitro hepatotoxicity mediated by CYP2E1, CYP2D6, and CYP3A4 metabolism. (November 2021) - Roque Bravo, Rita; Carmo, Helena; Valente, Maria João; Silva, João Pedro; Carvalho, Félix; Bastos, Maria de Lourdes; Dias da Silva, Diana
Abstract: 4-Fluoromethamphetamine (4-FMA) is an amphetamine-like psychoactive substance with recognized entactogenic and stimulant effects, but hitherto unclear toxicological mechanisms. Taking into consideration that the vast majority of 4-FMA users consume this substance through oral route, the liver is expected to be highly exposed. The aim of this work was to determine the hepatotoxic potential of 4-FMA using in vitro hepatocellular models: primary rat hepatocytes (PRH), human hepatoma cell lines HepaRG and HepG2, and resorting to concentrations ranging from 37 μM to 30 mM, during a 24-h exposure. EC50 values, estimated from the MTT viability assay data, were 2.21 mM, 5.59 mM and 9.57 mM, for each model, respectively. The most sensitive model, PRH, was then co-exposed to 4-FMA and cytochrome P450 (CYP) inhibitors to investigate the influence of metabolism on the toxicity of 4-FMA. Results show that CYP2E1, CYP3A4 and CYP2D6 have major roles in 4-FMA cytotoxicity. Inhibition of CYP2D6 and CYP3A4 led to left-geared shifts in the concentration–response curves of 4-FMA, hinting at a role of these metabolic enzymes for detoxifying 4-FMA, while CYP2E1 inhibition pointed towards a toxifying role of this enzyme in 4-FMA metabolism at physiologically-relevant concentrations. The drug also destabilised mitochondrial membrane potential and decreased ATP levels, increased the production of reactive oxygen and nitrogen species and compromised thiol antioxidant defences. 4-FMA further affected PRH integrity by interfering with the machinery of apoptosis and necrosis, increasing the activity of initiator and effector caspases, and causing loss of cell membrane integrity. Potential for autophagy was also observed. This research contributes to the growing body of evidence regarding the toxicity of new psychoactive substances, in particular regarding their hepatotoxic effects; the apparent influence of metabolism over the resulting cytotoxicity of 4-FMA shows that there is a substantial degree of unpredictability of the consequences for users that could be independent of the dose.